Pengaruh Penggunaan Tiktok terhadap Partisipasi Pemilih Muda dalam Pemilihan Presiden : (Studi Kasus pada Generasi Z pada Pemilu 2024 Kota Kupang) - Juannita Paulo Cicilia Da Cruz; Laurensius P. Sayrani; Jim Briand Kolianan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to examine the influence of TikTok usage on youth voter participation among Generation Z in the 2024 Presidential Election in Kupang City. TikTok, as one of the most popular social media platforms among young people, serves as a medium for spreading political information, forming political identity, and mobilizing political participation. Using a quantitative approach with a survey method involving 396 respondents, the data were analyzed using multiple linear regression. The results indicate that engagement with political content, political identity formation, and political mobilization through TikTok significantly influence youth voter participation. These findings affirm the strategic role of social media in enhancing political awareness and engagement among the younger generation.